A Zinc Phthalocyanine Based Periodic Mesoporous Organosilica Exhibiting Charge Transfer to Fullerenes. Issue 46 (7th October 2014) - Auras, Florian; Li, Yan; Löbermann, Florian; Döblinger, Markus; Schuster, Jörg; Peter, Laurence M.; Trauner, Dirk; Bein, Thomas
Abstract Periodic mesoporous organosilica (PMO) materials offer a strategy to position molecular semiconductors within a highly defined, porous network. We developed thin films of a new semiconducting zinc phthalocyanine‐bridged PMO exhibiting a face‐centered orthorhombic pore structure with an average pore diameter of 11 nm. The exceptional degree of order achieved with this PMO enabled us to create thin films consisting of a single porous domain throughout their entire thickness, thus providing maximal accessibility for subsequent incorporation of a complementary phase. The phthalocyanine building blocks inside the pore walls were found to be well‐aggregated, enabling electronic conductivity and extending the light‐harvesting capabilities to the near IR region. Ordered 3D heterojunctions capable of promoting photo‐induced charge transfer were constructed by impregnation of the PMO with a fullerene derivative. When integrated into a photovoltaic device, the infiltrated PMO is capable of producing a high open‐circuit voltage and a considerable photocurrent, which represents a significant step towards potential applications of PMOs in optoelectronics.